ECOLOGY-BASED SCHOOL PRINCIPAL LEADERSHIP MODEL TO IMPROVE THE QUALITY OF EDUCATION - Mulyadi, Budi; Suyata, Pujiati; Santosa, Achadi Budi (JURNAL EDUSCIENCE, 2025)
Purpose-Ecologically oriented leadership models are becoming increasingly important for fostering environmental awareness, integrating sustainability values into the curriculum, and building a school culture that values its ecosystem. This study aims to analyze the strategy, implementation, and impact of ecology-based principal leadership in building a sustainable school culture at SMA Negeri 6 Yogyakarta.Methodology-The approach employed was qualitative, utilizing a case study design that involved four key informants through in-depth interviews, non-participatory observations, and documentation studies. The data were analyzed using Miles and Huberman's model, which involves the stages of data reduction, data presentation, and data conclusion, by triangulating sources and methods to maintain credibility.Findings-The results of the study demonstrate that ecological leadership is implemented through an environmentally cultured vision and policies, the integration of ecological issues into the project-based curriculum, and the active participation of school residents in the Muda Wijaya Green School Community (MWGSC) program. Key supporting factors include the principal's commitment, collaboration among school residents, and external support, while constraints include limited resources and the adaptation of new students.Contribution-This model has been shown to have a positive impact on learning motivation, environmental care character, and the improvement of holistic education quality, while also highlighting the need for ecological leadership training and support for sustainable education policies in schools.